Capacity Building, Communication and Awareness Strategy : The Development of a National Framework for Weather, Water and Climate Services for Zambia - International Water Management Institute (2024)
Capacity building focuses on institutional, infrastructure, and human resource capacity whilst communication and awareness ensure that water, weather, and climate information and products reach the targeted audience and users. Awareness raising seeks to inform and educate Zambian people about the water, weather, and climate information to influence their decision-making process.